Evaluasi Efektivitas Manajemen Pembiayaan Pendidikan Menggunakan Model CIPP di Sekolah Menengah Atas Swasta - Riyanti, Triska; Nugraha, Mulyawan Safwandy (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
Education is one of the main pillars in sustainable national development. Effective financial management in schools is crucial to ensuring the quality of education, especially in private schools that often face challenges in managing resources. This study aims to evaluate the effectiveness of educational financial management at SMA PGRI Rancaekek using the Context, Input, Process, Product (CIPP) model. The research methodology is descriptive quantitative, with data collected through observations, questionnaires, and interviews with 50 purposively selected respondents. The findings reveal that the